The international meat trade - Spencer, Jennifer (Woodhead, 2003)
With recent crises in the meat supply chain in the UK and elsewhere, seldom has the international meat industry been subject to so much attention as it is in the opening years of the 21st century. This major looseleaf represents the first comprehensive overview of the meat industry worldwide, and looks at production, consumption, prices, trade and policy profiles and developments in the key jurisdictions for each of the major product groups - cattle, sheep, pigs and poultry. It provides a wealth of market statistics and analysis of trends, future outlook, threats and opportunities. This is an.